Increasing Single-Mode Power in VCSELs With Antiresonant Oxide Island - Marta Wieckowska; Maciej Dems (IEEE Photonics Journal)
This article focuses on increasing the single-mode power in Vertical Cavity Surface Emitting Lasers (VCSELs) through the strategic integration of an antiresonant oxide islands. Using a gallium arsenide-based VCSEL as a case study, we explore the influence of oxide island parameters on lateral mode discrimination in term of threshold currents and emitted powers. The analysis confirms non-uniform variations in threshold currents, with varying oxide island position and size. Leveraging the spatial hole burning effect, we compute the output power and identify optimal island configurations for maximizing single-mode power. The results showcase the efficacy of antiresonant oxide islands in significantly enhancing single-mode power output in VCSELs.